2002
DOI: 10.1161/01.cir.0000022018.68965.6d
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinases in Chronically Hypoxic Infant Human and Rabbit Hearts

Abstract: Background-Many infants who undergo heart surgery have a congenital cyanotic defect in which the heart is chronically perfused with hypoxic blood. However, the signaling pathways by which infant hearts adapt to chronic hypoxia and resist subsequent surgical ischemia is unknown. Method and Results-We determined the activation and translocation of protein kinase C (PKC) isoforms and mitogen activated protein kinases (MAP kinases) in 15 infants with cyanotic (SaO 2 Ͻ85%) or acyanotic (SaO 2 Ͼ95%) heart defects un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
44
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 28 publications
7
44
1
5
Order By: Relevance
“…[31][32][33] However, in this study, the I/R ratio of the rats exposed to low barometric pressure hypoxia was significantly higher than that of the rats pretreated with 1000 ppm CO. And the activation of MAPKs, Akt, and eNOS induced by hypoxia was significantly weaker than that induced by 1000 ppm CO. In addition, I/R ratio was significantly lower in the rats pretreated with 1000 ppm CO than in those pretreated with 500 ppm CO, although the concentrations of HbCO in blood were not significantly different between the 2 groups (30.1% and 24.9% at 24 hours of inhalation, respectively).…”
Section: Discussioncontrasting
confidence: 74%
“…[31][32][33] However, in this study, the I/R ratio of the rats exposed to low barometric pressure hypoxia was significantly higher than that of the rats pretreated with 1000 ppm CO. And the activation of MAPKs, Akt, and eNOS induced by hypoxia was significantly weaker than that induced by 1000 ppm CO. In addition, I/R ratio was significantly lower in the rats pretreated with 1000 ppm CO than in those pretreated with 500 ppm CO, although the concentrations of HbCO in blood were not significantly different between the 2 groups (30.1% and 24.9% at 24 hours of inhalation, respectively).…”
Section: Discussioncontrasting
confidence: 74%
“…By elucidating the impact that prolonged periods of hypoxemia exert upon resistance to subsequent ischemia, we should be able to understand and improve cardioprotection in children with congenital heart defects. Recently we showed that infant human and rabbit hearts adapt to chronic hypoxemia by activation of PKC ⑀ , 1 p38 MAPK, and JNK signaling pathways (1). As chronic hypoxemia in rabbits induces changes in the heart similar to that found in humans, the rabbit may be useful to test other adaptive mechanisms thought to occur in human.…”
mentioning
confidence: 99%
“…Overexpression of mRNA for Hsp70 using gene therapy translates to increased Hsp70 protein levels that are associated with increased cardioprotection, suggesting this stress protein plays an important role in mediating resistance to myocardial ischemia (6). Adaptation to the stress of chronic hypoxia also results in increased cardioprotection (1,8). We therefore reasoned that adaptation to chronic hypoxia would result in increased expression of mRNA and subcellular redistribution of Hsp70 protein.…”
mentioning
confidence: 99%
“…4 Exposure of animals to chronic systemic hypoxia also induces protection against myocardial ischemia, although the mechanisms are poorly characterized. [5][6][7] Hypoxia-inducible factor 1 (HIF-1) activates the transcription of genes whose protein products mediate adaptive responses to hypoxia/ischemia, including erythropoietin (EPO), glucose transporter 1 (GLUT1), nitric oxide synthase 2 (NOS2), and vascular endothelial growth factor (VEGF). 8 HIF-1 consists of a constitutively expressed HIF-1␤ subunit and an O 2 -regulated HIF-1␣ subunit.…”
mentioning
confidence: 99%